ANALISIS EKONOMI PENGGUNAAN ALAT PENYULINGAN NIRA AREN MENJADI BIOETANOL DI KELOMPOK TANI HUTAN TEYAPU DI DESA TALAWAAN KECAMATAN TALAWAAN KABUPATEN MINAHASA UTARA - Novan G. Sumampow; Robert Molenaar; Frans Wenur (COCOS, 2022)
ABSTRACTThe purpose of this study is to calculate what the total cost per hour at each nira arendistillery, and also to calculate the economic feasibility value of the distillation tool The benefitof this study is to provide information on the total cost per hour and economic feasibility ofoperating a distillation tool or distillery nira aren into bioethanol. The results of this studyresulted in a total cost of Rp. 69,721 / hour, and the results of the Break Even Point (BEP)calculation based on working hours of 1,456 / year were 6756.60 liters / year or equivalent toRp. 19,785,287 / year. Feasibility analysis based on Net Present Value (NPV) calculations wasobtained at Rp.293,576,173.87, and Internal Rate of Return (IRR) of 63%, and Benefit/CostRatio (B/C Ratio) of 1.36.Keywords : Economic Analysis of The Use of Nira Aren Distillery Into Bioethanol